Efficacy of Furosemide in Methotrexate Clearance in Patients Treated with High Dose Methotrexate: A Cohort Study - Muhammad Tariq, Sehrish Sarwar Baloch, Saqib Raza Khan, Mehwish Shahzadi, Mohammad Daanyaal Khan, Muhammad Jawad Zahid, Samad Jehangir Shah, Yasmin Abdul Rashid (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Methotrexate was first used in 1947 as a chemotherapeutic drug in the treatment of acute lymphoblastic leukemia (ALL). Methotrexate has been extensively explored as an anticancer drug since that time. High dose methotrexate is a term used for doses above 1000mg/m2. Objective: To determine efficacy of Furosemide in methotrexate clearance in patients treated with high dose methotrexate Methodology: The current study was prospective cohort study carried out at the Oncology department of tertiary care hospitals of Peshawar for a period of one year from January 2020 to January 2021. A total of 80 patients were enrolled in the study. All patients received daily hydration of at least 5 liters along with urine alkalization with sodium bicarbonate and on calcium rescue as per protocol. All patients were given Furosemide 40 mg three times a day. Methotrexate levels were monitored every 24 hours to follow its clearance. All the Data analysis was done by using IBM SPSS version 24. Results: The mean (SD) hospital stay in the current study was 4 (±1) days. Frequency of delayed methotrexate clearance was observed in 16 (20%) patients. The mean (SD) time of methotrexate clearance was 4 (±1) days. Renal injury was observed in 8 (10%) subjects, electrolyte imbalance in 12 (15%) subjects, transaminitis in 11 (13.75%) subjects while mucositis was observed in 8 (10%) subjects. Conclusion: Our study concludes that furosemide is highly effective in methotrexate clearance in patients treated with high dose methotrexate. The use of furosemide reduces the cost and hospital stay. As furosemide is cheaper and easily available so it can be used easily in the methotrexate clearance.